2015
DOI: 10.18203/2320-6012.ijrms20151180
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning versus lecture-based learning in pharmacology in a junior doctor teaching program: a crossover study from northern India

Abstract: Background:The undergraduate MBBS training in our country is still in the traditional mode. The main part of the curriculum consists of lecture, tutorial, practical and ward teaching classes with a limited number of problem based session. The objective of the study was undertaken to compare PBL with LBL in terms of students' knowledge retention in the subject of Pharmacology in undergraduate medical training. Methods: The current survey was planned and executed by the Department of Pharmacology in collaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The results were consistent with the study by Imran et al, where case-based learning group had more retention of knowledge. 7 This is one of the few studies that showed that the Problem based learning had better outcome than other methods of learning.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results were consistent with the study by Imran et al, where case-based learning group had more retention of knowledge. 7 This is one of the few studies that showed that the Problem based learning had better outcome than other methods of learning.…”
Section: Resultsmentioning
confidence: 96%
“…6 Case based learning is an efficient teaching learning method in terms of retention of knowledge. 7 According to a study student in the problem based group gained more knowledge and had higher motivation toward learning compared to students in the lecture group. 8 Sunil Nettath evaluated the efficacy of problem-based learning in 13 medical students using problem-case scenario.…”
mentioning
confidence: 99%
“…These results are in accordance with previous studies, the PBL method helps students understand the information provided. In addition, PBL makes students more interested in participating in learning, develops independent learning skills, develops the scope of knowledge, and develops analytical skills (Huo, Yang, & Gong, 2016;Imran et al, 2015;Pan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study from North India also found that the students who underwent PBL obtained higher mean scores as compared to their counterparts who were exposed to LBL. 16 A study from Peshawar, Pakistan, on 146 thirdyear MBBS students concluded that PBL was more effective than LBL in the academic performance of medical students since the mean scores in the former group were higher. 17 Similar results have been reported by comparative studies from England and The Netherlands.…”
Section: Discussionmentioning
confidence: 99%